Model Pengembangan SKL Berbasis SPMI untuk Meningkatkan Mutu Pendidikan di SDIT Nurul Ishlah Kota Banda Aceh - Huriana, Dian; Mardhatillah, Mardhatillah; Sariakin, Sariakin; Sari, Siti Mayang (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to develop SKL (Graduate Competency Standards) based on SPMI (Internal Quality Assurance System). This research was conducted at Nurul Ishlah Integrated Islamic Elementary School in Banda Aceh City. This research uses the Research and Development (R&D) method, which is a process or steps to develop a new product or perfect an existing product. The data collection techniques used in this study were through observation, questionnaires, and interviews. Data analysis was carried out descriptively to obtain data on SPMI-based SKL. The results of the study proved that the SPMI-Based SKL Development Model to Improve the Quality of Education at SDIT Nurul Ishlah in Banda Aceh city, which was compiled by the school in addition to referring to the Minister of National Education Regulation number 20 of 2016, also refers to the quality standard curriculum of Integrated Islamic Schools (SIT) which is then used as Quality Assurance for graduates at SDIT Nurul Ishlah, involving 2 categories, namely akhlak karimah (prayer with awareness,  fond of reading the Quran, devoted to parents, discipline, confident, polite and polite, clean and healthy culture, honest) and optimal academic achievement (tartil reading the Quran, complete the field of study, memorize the three juz of the Quran, communicate well and read effectively